Evaluation of a pre-surgical functional MRI workflow: From data acquisition to reporting. (February 2016) - Pernet, Cyril R.; Gorgolewski, Krzysztof J.; Job, Dominic; Rodriguez, David; Storkey, Amos; Whittle, Ian; Wardlaw, Joanna
Highlights: Operational definition of clinical fMRI protocols. Validation of single subject fMRI protocol and dedicated data analysis. Automated data analysis to aid brain tumour surgical planning. Validation of fMRI results in patients vs. direct electrical stimulation. Abstract: Purpose: Present and assess clinical protocols and associated automated workflow for pre-surgical functional magnetic resonance imaging in brain tumor patients. Methods: Protocols were validated using a single-subject reliability approach based on 10 healthy control subjects. Results from the automated workflow were evaluated in 9 patients with brain tumors, comparing fMRI results to direct electrical stimulation (DES) of the cortex. Results: Using a new approach to compute single-subject fMRI reliability in controls, we show that not all tasks are suitable in the clinical context, even if they show meaningful results at the group level. Comparison of the fMRI results from patients to DES showed good correspondence between techniques (odds ratio 36). Conclusion: Providing that validated and reliable fMRI protocols are used, fMRI can accurately delineate eloquent areas, thus providing an aid to medical decision regarding brain tumor surgery.